IL-10-producing Th1 cells possess a distinct molecular signature in malaria - Chelsea L. Edwards; Susanna S. Ng; Fabian de Labastida Rivera; Dillon Corvino; Jessica A. Engel; Marcela Montes de Oca; Luzia Bukali; Teija C.M. Frame; Patrick T. Bunn; Shashi Bhushan Chauhan; Siddharth Sankar Singh; Yulin Wang; et al. (The Journal of Clinical Investigation, 2023)
Control of intracellular parasites responsible for malaria requires host IFN-γ+T-bet+CD4+ T cells (Th1 cells) with IL-10 produced by Th1 cells to mitigate the pathology induced by this inflammatory response. However, these IL-10–producing Th1 (induced type I regulatory [Tr1]) cells can also promote parasite persistence or impair immunity to reinfection or vaccination. Here, we identified molecular and phenotypic signatures that distinguished IL-10–Th1 cells from IL-10+Tr1 cells in Plasmodium falciparum–infected people who participated in controlled human malaria infection studies, as well as C57BL/6 mice with experimental malaria caused by P. berghei ANKA. We also identified a conserved Tr1 cell molecular signature shared between patients with malaria, dengue, and graft-versus-host disease. Genetic manipulation of primary human CD4+ T cells showed that the transcription factor cMAF played an important role in the induction of IL-10, while BLIMP-1 promoted the development of human CD4+ T cells expressing multiple coinhibitory receptors. We also describe heterogeneity of Tr1 cell coinhibitory receptor expression that has implications for targeting these molecules for clinical advantage during infection. Overall, this work provides insights into CD4+ T cell development during malaria that offer opportunities for creation of strategies to modulate CD4+ T cell functions and improve antiparasitic immunity.